Surveillance of Wuchereria bancrofti infection by anti-filarial IgG4 in urine among schoolchildren and molecular xenomonitoring in Sri Lanka: a post mass drug administration study - Hidekazu Takagi; Thishan C. Yahathugoda; Bumpei Tojo; Upeksha L. Rathnapala; Fumiaki Nagaoka; Mirani V. Weerasooriya; Makoto Itoh (Tropical Medicine and Health, 2019)
Abstract Background Surveillance of hidden foci or resurgence of the bancroftian filariasis has high priority to maintain the elimination status in Sri Lanka. For the surveillance, two methods were applied in Matotagama, Matara, Sri Lanka; (i) molecular xenomonitoring (MX) by PCR to detect parasite DNA in the vector, Culex (Cx) quinquefasciatus and (ii) survey of anti-filarial IgG4 in urine samples from schoolchildren. Results Mosquitoes were collected monthly from index houses for 17 months (2013 to 2014) to confirm the existence of bancroftian parasite. Index houses in Matotagama had recorded microfilaria-positive cases in the recent past. Five schools were selected considering Matotagama as the catchment area and all students who presented on the day were tested for urine anti-filarial IgG4 in 2015. Wuchereria bancrofti DNA in Cx. quinquefasciatus pools were found in 14 of 17 months studied and ranged between 0 and 1.4%. The MX rate was greatly increased at least two times in the year following the driest months (March, August). A total of 735 schoolchildren were tested for urine anti-filarial IgG4. Three schools located closer to the MX area had higher positive rates, 3.4%, 3.6%, and 6.6%. Both highest positive rates of MX and urine were located in a nearer vicinity. Conclusion Monthly collections to study lymphatic filariasis (LF) transmission by MX was conducted for the first time in Sri Lanka. We observed that the filarial DNA-positive rate had an association with seasonal cycle of precipitation. More than 1% filarial DNA and > 5% anti-filarial antibody rates confirmed ongoing transmission in Matotagama. The combination of two non-invasive surveys, the urine anti-filarial IgG4 levels of schoolchildren and MX of vector mosquitoes, would be a convenient package to monitor the ongoing transmission (hotspots) of LF in the surveillance.